A new finding for carbon nanotubes in polymer blends: Reduction of nanotube breakage during melt mixing. (January 2018) - Guo, Jiaxi; Briggs, Nicholas; Crossley, Steven; Grady, Brian P
High aspect ratio multi-walled carbon nanotubes (MWCNTs) having an average length of 4.23 μm and an average diameter of 9.5 nm have been melt mixed with immiscible polystyrene/poly(methyl methacrylate) (PS/PMMA) blends in mass ratio 80:20 and 20:80, respectively. The carbon nanotubes (CNTs) reside in the PMMA phase, and length analysis after melt mixing indicates that when PMMA was the minor phase (20 wt%), little or no CNT breaking occurred during mixing. On the other hand, when PMMA was the major phase (80 wt%), the average length of the CNTs was reduced to 2.78 μm, approximately 70% of their original length. Mixing the CNTs with neat PMMA under the same mixing conditions resulted in a reduction in CNT length to 1.02 μm, only 24% of the original length. Electrical conductivity results show that less CNT breakage leads to a reduction by a factor of 2.5 in the electrical percolation threshold in the 20:80 PMMA/PS blend polymer, which is much larger than a simple volume fraction argument would suggest. This article shows for the first time that relatively long MWCNTs break less in polymer blends than in the neat polymer with concomitant reductions in percolation threshold.